Culture Methods for Isolation of Canine Hair Follicle Stem Cells (CHFSC) - Hemavathi, N. (Indian Journal of Veterinary Anatomy, 2020)
Adult stem cell models are important tools interacting in tissues, replacing animal experimental studies for understanding the basis of physiology and therapeutics. In this study, we aimed to isolate and culture stem cells from canine hair follicular tissue in vitro by three methods viz, explants cuture, microdissection and filtrate culture methods. Dispase II enzymatical digestion gave higher cell yield (3.08 ± 0.47×106) than trypsin/EDTA enzymatical digestion of canine skin samples. Filtrate culture method gave high cell yield among three different culture methods. In microdissection method, colony forming unit (CFU) and colony size of cells from isthmus fragment were 14.71 ± 1.57 in numbers and 11.21 ± 2.45 mm- 2 respectively which was significantly higher than other fragments of hair follicle (P<0.01). We concluded that the dispase II enzyme digestion and filtrate culture method was the best method to isolate cHFSCs.